Analisis Tingkat Kekeringan untuk Mengurangi Resiko Gagal Panen Tanaman Pangan di Provinsi Banten - Taufan Hidayat; Yonny Koesmaryono; Aris Pramudia (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Analysis of Drought Level to Reduce Risk of Food Crop Harvest Fails in Banten ProvinceABSTRACT. Climate is one of the most important factor to the success of the agriculture production. Climate variability such as season change, lack or excess of water, are sample examples of climate factors which limit agriculture production. Planning agriculture activities which involving climate factors as one of the consideration will reduce crops production failure. This research conducted to identified the potency of drought at Banten Province by consecutive dry days analysis at 5, 10, and 15 continuous days or more. The result showed that the potency of drought at northern Banten is higher compared to middle and southern Banten. This was showed by the high opportunities of DHK = 5, 10, and 15 continuous days or more, as big as 0,65, 0,46, and 0,28. The lowest potency of drought occur at southern Banten with opportunities of DHK≥ 5, 10, and 15 continuous days or more, each as big as 0,43, 0,30, and 0,18.